Osteotomy and Filling for Osteochondral Lesions of the Tibial Plafond: A Novel Morphology Based Surgical Technique - Quinten Rikken MD; Julian Hollander; Bsc Jari Dahmen MD; Gino M M.M.J. Kerkhoffs MD, PhD; Sjoerd Stufkens MD, PhD (Foot & Ankle Orthopaedics)
Category: Ankle Introduction/Purpose: Symptomatic primary (large) cystic and non-primary osteochondral lesions of the medial and central tibial plafond are challenging entities to treat. These lesions may benefit from a lesion specific treatment approach. In the present manuscript we describe the novel surgical technique by means of an osteotomy of the distal tibia and cancellous bone graft filling. The procedure involves an oblique distal tibia osteotomy which is made directly over the lesion. Hereafter, the defective lesion tissue is curetted and filled with autologous cancellous bone from the ipsilateral iliac crest, and compression by means of refixation of the osteotomy. The procedure provides provide surgeons an alternative option for OLTP. Methods: Indications: Symptomatic primary cystic and non-primary (i.e., failed prior surgical treatment for the OLTP) osteochondral lesions of the medial and central tibial plafond which failed to respond to a minimum 6 months of nonoperative treatment. Results: Surgical Technique: The procedure is started by means of a curved incision over the medial malleolus, and careful dissection until adequate visualization of the medial malleolus and anteromedial ankle joint is achieved. Hereafter, the screws for the fixation of the osteotomy are predrilled. Then, the OLTP is directly approached with an osteotomy using an oscillating saw directly through the lesion. The lesion is thereafter debrided with a curette until healthy bleeding bone is observed. Subsequently, microfracturing may be performed. Then, autologous cancellous bone is harvested from the ipsilateral iliac crest (or from the osteotomy site in small cysts) and the cyst is filled. Finally, the osteotomy is closed and fixated with two diverging 3.5mm cortical lag screws. Conclusion: Postoperative Management: Post-operatively, there is a period of 5-6 weeks in short leg cast non-weight bearing and 5-6 weeks of short leg cast with weightbearing as tolerated. Hereafter, a CT-scan is made to confirm osteotomy union and patients start a personalized rehabilitation under the guidance of a physical therapist.